Health care needs, utilization and barriers in Croatia : regional and urban-rural differences - Pristaš, Ivan (Array, 2009)
Summary: Even the most socially aware countries in the World have noticed the gap increase between the poorest and the richest population groups. The purpose of this study was to investigate the presence of inequity and to identify main barriers for equitable health care utilization by economic status, region and area of living, controlled for health needs in the Croatian adult population. The data from the Croatian Adult Health Survey 2003 were used in this study. The results show that among the respondents with higher health needs, those with economic status above average had higher proportion of regular annual general practitioner and medical specialist visits. In contrast, highly frequent visits to physician were more common in respondents who were below average economic status. Economically worse-off women, regardless on their health care needs reported gynecologist visits less regularly than the better-off women. Long waiting and the large distance from the health care facilities were the most commonly reported barriers in health care utilization. High expenses were present as the main barrier at dentist and inpatient health services utilization. Suburban and rural settlements were more burdened with long distance from the health care facilities and high expenses for all health services, aggravated by the long waiting time for visits to GP. Respondents from the urban settings reported long waiting time and unkindness of the health personnel as the main barriers. The results of this study clearly show the main barriers in the equitable health care delivery to Croatia population from the health care users perspective